(untitled) (Perner’s Contacts, 2009)
The topic of the paper is traffic solution proposal for Studentska Street in area of University of Pardubice. The time horizon of the study is 2025, when construction of the Studentska Street extension and housing development in locality Cihelna is scheduled. Studentska Street will serve as bypass of the I/36. There are suggested describes five options of traffic solutions for 2025 based on traffic inputs analysis. The options are evaluated in agreement with CSN 73 6102 and through the use of VISSIM micro simulation.